Development Of Water Quality Monitoring For Smart Aquaculture System - Hamid, Mohd Saad; Abd Wahab, Muhammad Amirul; Abdullah, Rasyidah; Abd Gani, Shamsul Fakhar; Hamzah, Rostam Affendi (Medwell Journals, 2019)
Water quality monitoring for smart aquaculture system is a device that helps to describe the water quality parameter such as pH, turbidity and temperature of the water. It will monitor the process of sampling and analysing the water condition. This project is focused on local aquaculture species. Water quality monitoring for smart aquaculture system is designed to allow fish farmers to monitor and control their fish in the pond much more easily than before. It will help fish farmers to understand more about the water quality parameter that needed for their fish. It is equipped with an early warning detection that can help fish farmers monitoring their pond. The data collected will be transmitted to the cloud server and user will get notifications regarding the condition of their pond by using push notification services to their smartphone. This can enhance the productivity of the fish pond because user can always monitor the level of water quality that suitable with the fish. This study proposed a monitoring system with the ability to measure temperature, pH, turbidity and water level. The ability of the system to provide information and notification proven when the system sent a notification from Raspberry Pi board to smartphone where the pH level of the water beyond the allowable range. User also, able to control water pump to control the water over wireless connection using Blynk platform. Finally, the system successfully embedded new technology to help to revolutionize the aquaculture industry with the help of internet of things technology.